The quest of the missing map - Keene, Carolyn (New York, Grosset & Dunlap, 1997)
The eighteen-year-old girl detective must find a man who has been missing for years in order to locate the other half of a treasure map.
730
730
Accelerated Reader AR
Keywords: Drew, Nancy -- (Fictitious character) -- Juvenile fiction; Drew, Nancy -- (Fictitious character) -- Fiction; Treasure troves -- Juvenile fiction; Mystery and detective stories; Buried treasure -- Fiction; Mystery fiction